Caregivers and Their Support Networks. Who Supports Whom? Different Models of Informal Networks - Bramanti, Donatella; Carradore, Marco (Italian Sociological Review, 2025)
Increases in life expectancy mean that more elderly people require care. This has significant implications for carers, who are typically women belonging to the so-called ‘sandwich generation’. This research, which formed part of a national mixed-methods study conducted in Italy between 2024 and 2025, aimed to identify the role of informal social relationships in supporting carers of older people. Data were collected from twenty caregiver-supporter dyads, in which the caregivers were aged between 50 and 65. In the first of two online interviews, the caregivers were interviewed using social network analysis tools to identify their support networks (i.e. the network structural data). In the second interview, qualitative data were gathered from the caregiver and their prime supporter (for example, a spouse, relative, or friend), and evaluated using thematic and template analysis. The results emphasise the variety of caregiving network models (for example, low-density large networks; high-density large networks; and low-density small networks) and the different roles caregivers can play within their networks. Their role depends on the type of support their receive. However, even caregivers situated within large functional networks may find that their resources are insufficient. These findings suggest that open networks and ‘bridging social capital’ contribute to greater well-being in both the caregivers and their supporters. Thus, promoting and preserving bridging social capital is crucial to enhancing the well-being of all actors involved in informal caregiving.